Childhood Sexual Abuse and Associated Suicidal Ideation and Attempts Among Gay and Bisexual Men in China: A Moderated Mediation Model - Xue, Shuang (Journal of interpersonal violence, 2023)
Childhood sexual abuse (CSA) is a critical risk factor for suicidal ideation and attempts, especially among gay and bisexual men who experience living as a minority. However, whether internalized homophobia (IH) underlies suicide risk and the role of outness to one’s family in this association warrants investigation to inform preventive interventions. Using a cross-sectional survey of 570 gay and bisexual men in China, we examined the relationship between CSA and suicidality in the Chinese context and tested a moderated mediation model in this relationship. Nearly 65.6% of the participants had experienced suicidal ideation and 36.8% had attempted suicide. Participants with a history of CSA had higher suicidal ideation (r = 0.33, p < .01) and attempts (r = 0.48, p < .01). Our bootstrapped mediation analysis showed that IH partially mediated the relationship between CSA and suicidal ideation and attempts. Moreover, outness to one’s family (parents and other family members) strengthened the direct association of CSA and IH, and the indirect relationship between CSA and suicidal ideation and attempts. These findings highlight the significance of identifying risk factors and mechanisms for suicidality among Chinese gay and bisexual men, suggesting the importance of early intervention, especially for those who have experienced CSA, to eliminate their IH and to improve family support for coming out to prevent the onset of suicidal ideation and attempts.